Gender Transformations in Prehistoric and Archaic Societies - Koch, Julia Katharina (Scales of Transformation Ser., 2020)
In which chronological, spatial, and social contexts is gender a relevant social category that is noticeable in the archaeological material? How can transformations in social gender relations and identity be recognized archaeologically? Is the identity of prehistoric people defined by gender? If so, what is the accompanying cultural context? What about gender equality among the scientists working in archaeology? In what degree are research teams, as well as their scientific approaches, biased today?These and other burning questions are intensively discussed in this volume, which comprises 25 c.